How Does Sustainable Energy System, Creativity, and Green Finance affect Environment Efficiency and Sustainable Economic Growth: Evidence from Highest Emitting Economies - Yunus, Lukman; Iswandi, Marsuki; Baco, La; Zani, Munirwan; Limi, Muhammad Aswar; Sujono, Sujono (International Journal of Energy Economics and Policy, 2023)
In present times, sustainability is to be demanded to attain high economic growth in longer run. Thus, countries are obliged to scrutinize the factors which balance the economic growth and prove to be efficient indicator of environment. This study, knowing the significance of such indicators, the study formulates a framework in which a role of sustainable energy system, creativity, and green finance on the environmental efficiency and sustainable economic development intends to be examined in the context of high carbon emission economies such as Iran, Canada, China, Indonesia, India, Japan, Saudi Arabia, United States, Russia, and South Korea. In order to tackle the abovementioned issue, the study used the data extracted from world development indicators (WDI) covering the period from 2010 to 2020. The study employed Random fixed model to test the proposed hypotheses. Obtained results expose that sustainable energy systems, creativity and green finance share negative association with carbon emissions, hence, revealing this point that the indicators are useful to increase sustainable economic development and environmental efficiency. Thereby, in order to achieve sustainable economic growth, governments are liable to implement policies with a long-term approach. The outcomes are also helpful for the upcoming researchers and regulators while formulating the policies about environmental efficiency.